2014
DOI: 10.1002/ana.24285
|View full text |Cite
|
Sign up to set email alerts
|

Are acute infarcts the cause of leukoaraiosis? Brain mapping for 16 consecutive weeks

Abstract: Neuroimaging of older adults commonly reveals abnormality (leukoaraiosis) in the cerebral white matter. Studies have established that extensive leukoaraiosis predicts dementia and disability, but the pathogenesis of leukoaraiosis remains unclear. We recruited 5 patients with leukoaraiosis and performed magnetic resonance mapping of the brain for 16 consecutive weeks. We observed tiny lesions arising de novo in the cerebral white matter. These lesions were clinically silent. They had the signature features of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 34 publications
5
56
1
Order By: Relevance
“…5,6 Recent findings link WMHs to an accumulation of tiny infarctions, 34 which could cause such tissue damage. However, WMHs primarily develop in regions with low perfusion, suggesting that low perfusion is involved in WMH conception.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Recent findings link WMHs to an accumulation of tiny infarctions, 34 which could cause such tissue damage. However, WMHs primarily develop in regions with low perfusion, suggesting that low perfusion is involved in WMH conception.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent evidence has shown that accumulation of microinfarcts may lead to the development of WMHs. 36 Recent research using transcranial Doppler ultrasound found that arterial stiffening reduces damping of the arterial waveform and increases cerebral pulsatility, which may damage small vessels, increase shear stress, and exacerbate impaired CVR. 37 Another factor influencing arterial pulsations, venous collagenosis, is a mechanical consequence of increased cerebral pulsatility and mechanical fatigue of vascular smooth muscles.…”
Section: Methods Participant Recruitment and Assessmentmentioning
confidence: 99%
“…6 PVWMH have recently been shown to develop by acute infarction adjacent to older lesions with extension occurring proximally towards the cortical surface favoring cortical arterial disease and hypoperfusion as an important cause. 7,8 We hypothesized that measuring PVWMH burden would provide a quantitative measure of cortical arterial disease and facilitate exploration of associations with cerebral amyloid deposition. Therefore, in the Alzheimer's Disease Neuroimaging Initiative (ADNI) cohort, we investigated the association between CSF and PET markers of elevated Ab and PVWMH.…”
mentioning
confidence: 99%